Climate-mediated shifts in Neandertal subsistence behaviors at Pech de l'Azé IV and Roc de Marsal (Dordogne Valley, France). Issue 96 (July 2016) - Hodgkins, Jamie; Marean, Curtis W.; Turq, Alain; Sandgathe, Dennis; McPherron, Shannon J.P.; Dibble, Harold
Abstract: Neandertals disappeared from Europe just after 40, 000 years ago. Some hypotheses ascribe this to numerous population crashes associated with glacial cycles in the late Pleistocene. The goal of this paper is to test the hypothesis that glacial periods stressed Neandertal populations. If cold climates stressed Neandertals, their subsistence behaviors may have changed—requiring intensified use of prey through more extensive nutrient extraction from faunal carcasses. To test this, an analysis of Neandertal butchering was conducted on medium sized bovid/cervid remains composed of predominately red deer ( Cervus elaphus ), reindeer ( Rangifer tarandus ), and roe deer ( Capreolus caprelous ) deposited during global warm and cold phases from two French sites: Pech de l'Azé IV (Pech IV, Bordes' excavation) and Roc de Marsal (RDM). Analysis of surface modification on high survival long bones and proximal and middle phalanges demonstrates that skeletal elements excavated from the cold levels (RDM Level 4, Pech IV Level I2) at each cave have more cut marks and percussion marks than elements from the warm levels (RDM Level 9, Pech IV Level Y-Z) after controlling for fragment size. At both sites, epiphyseal fragments are rare, and although this pattern can result from carnivore consumption, carnivore tooth marks are almost nonexistent (<0.1%). Alternatively, processing epiphyseal ends for bone grease may have been a Neandertal survival strategy, and epiphyses were more intensively percussed in cold levels than in warm levels at both RDM and Pech IV. The exploitation of low marrow yield elements such as phalanges does not show a consistent pattern relating to climate, but may have been a general Neandertal behavioral characteristic, suggesting that these hominids were regularly on the edge of sufficient nutrient availability even during interglacials. Overall, the faunal assemblages from Roc de Marsal and Pech IV provide some support for the hypothesis that Neandertals were processing faunal remains more heavily during glacial periods, suggesting a response to increased nutritional stress during colder time periods.